PERKEMBANGAN PERMASALAHAN DAN KENAKALAN REMAJA - Ainun Jariyah; Adolfin Keke; Melkior Bala Hayon (Jurnal Bionatural, 2025)
Adolescence is a Crucial transitional phase in human life, marked by complex biological, psychological, and social changes. On one hand, adolescents demonstrate great potential in the development of personality and self-identity; on the other hand, they are vulnerable to various issues that may lead to deviant behaviors such as juvenile delinquency. These problems not only affect the individuals themselves but also have broader impacts on families and society. This study comprehensively examines the dynamics of adolescent development, various forms and causes of adolescent problems, and applicable solutions to address juvenile delinquency through preventive, curative, corrective, and preservative approaches. Internal factors such as identity crises, internal conflicts, and emotional instability, along with external factors such as dysfunctional families, negative social environments, and media influence, are the primary causes of adolescent problems (Desmita, 2011; Hurlock, 1994; Prasasti, 2017). In tackling juvenile delinquency, active involvement from families, schools, and communities is required through a holistic approach that includes building harmonious family environments, applying fair discipline in schools, and fostering character in social settings (Mahesha et al., 2024; Karlina, 2020). The findings of this study indicate that integrated, cross-sectoral collaboration strategies can significantly reduce the rate of juvenile delinquency and promote positive adolescent development. Keywords: adolescent development, youth problems, juvenile delinquency, preventive solutions, social approach.